Metode Cutting Plane dan Analisis Sensitivitas pada Optimasi Keuntungan Penjualan Usaha Kue Putu Asli M*R - Moni Sarisa; Dewi Murni (UNIVERSITAS NEGERI PADANG, 2022)
The M*R Original Putu Cake business is located in Balingka village, IV Koto District, Agam Regency, West Sumatra. This business produces three types of putu cakes, namely white baked putu, black baked putu, and steamed putu. The purpose of this study is to determine the optimal amount of production using the cutting plane method and to determine the range of changes that can be made to the production factors using sensitivity analysis. The result gives, the optimal production quantities of white baked putu, black baked putu, and steamed putu are 9.998 packs, 4.835 packs, and 3.000 packs, respectively. Meanwhile, through sensitivity analysis, it is concluded that changes in production factors will not affect the optimal solution as long as it is within the range of the maximum upper limit and minimum lower limit according to the calculated output.